2011
DOI: 10.1159/000324559
|View full text |Cite
|
Sign up to set email alerts
|

Dental Enamel Structure Is Altered by Expression of Dominant Negative RhoA in Ameloblasts

Abstract: Using in vitrotooth germ cultures and analysis by confocal microscopy, ameloblasts treated with sodium fluoride were found to have elevated amounts of filamentous actin. Because this response is reduced by inhibitors of the Rho/ROCK signaling pathway, we generated mice that express dominant negative RhoA (RhoADN) in ameloblasts for in vivo analysis. Expression of the EGFP-RhoADN fusion protein was evaluated by RT-PCR and immunohistochemistry, and teeth were analyzed by scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Previous in vivo studies done with RhoA DN transgenic mice that express RhoA with a dominant negative N19 mutation to decrease RhoA activity in ameloblasts [Qiu et al, 1995] concluded that interference with RhoA activity leads to surface defects in enamel [Li et al, 2011a]. Because the defects seen in RhoA DN transgenic mice were somewhat similar to those seen in cases of human enamel fluorosis, in the present study ALCs were treated with NaF to determine if the cultured cells respond through cell signaling pathways and how treatment affects the cross-talk between Wnt and Rho in ameloblast cells, leading to alterations in pathway component expression or activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous in vivo studies done with RhoA DN transgenic mice that express RhoA with a dominant negative N19 mutation to decrease RhoA activity in ameloblasts [Qiu et al, 1995] concluded that interference with RhoA activity leads to surface defects in enamel [Li et al, 2011a]. Because the defects seen in RhoA DN transgenic mice were somewhat similar to those seen in cases of human enamel fluorosis, in the present study ALCs were treated with NaF to determine if the cultured cells respond through cell signaling pathways and how treatment affects the cross-talk between Wnt and Rho in ameloblast cells, leading to alterations in pathway component expression or activity.…”
Section: Discussionmentioning
confidence: 99%
“…The RhoA DN (dominant negative RhoA) plasmid includes amelogenin regulatory sequences and partially blocks endogenous RhoA in ameloblasts by the N19 dominant negative mutation [Qiu et al, 1995;Li et al, 2011b]. Four micrograms of RhoA DN plasmid was transfected to the RhoA pathway blocking groups using 10 μl of Lipofectamine 2000 in serum-free Opti-MEM (Invitrogen).…”
Section: Treatment With Rhoa Dn Plasmid and Rock Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…The transgenic mice in which dominant-negative T19N RhoA was expressed under the control of the amelogenin regulatory sequences showed enamel hypoplasia and surface defects in the molar cusps [17], [18]. In the Tg molar, amelogenin, E-cadherin, and Ki67 (proliferation marker) were reduced, and both canonical and noncanonical Wnt signaling pathways were activated [17], [19].…”
Section: Implication Of Rho Gtpases Signaling In Ameloblastsmentioning
confidence: 99%
“…Further, they are involved in osteoclastogenesis as well as in hematopoiesis and hemopathies [12], [13]. Recently, evidence has emerged showing the involvement of Rho signaling in tooth development [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24]. In this article, we summarize some interesting recent findings that provide molecular insights into how signaling by Rho GTPases results in tooth development, focusing on ameloblast differentiation in particular.…”
Section: Introductionmentioning
confidence: 99%